Brand Image of a Global Automotive Brand: Does Marketing Mix still Work the Charm? - Gani, Ackhriansyah Ahmad; Ghani, Amirul Haqeem Abd; Kamase, Jeni; Gani, Agung Achmad; Gani, Pratiwi Juniar Achmad (Jurnal Minds: Manajemen Ide dan Inspirasi, 2024)
This study explores how the brand image of a legacy automaker like Toyota adapts in the face of increasing competition in eco-friendly vehicles and advanced technology. We examine how customers perceive Toyota's product quality and pricing strategies in relation to brand image and purchase decisions. Through a survey of 170 customers, we utilize a covariance-based structural equation model (CB-SEM) to analyze the data. Interestingly, our findings suggest that product quality does not directly influence brand image, nor does it have an indirect effect on buying decisions. However, other hypothesized relationships within the model were supported. This implies that for established brands like Toyota, price competitiveness might be a more significant factor for a large segment of their customer base. Toyota's focus on price competitiveness could potentially deter new entrants, allowing them to refine their offerings with more strategic pricing.